Turismo, desenvolvimento local e sustentabilidade: um estudo de caso no município de Itatiaia - RJ - Rocha, Margarida Maria de Fraga (2005)
The extraordinary economic performance of the tourist industry worldwide in the second half of the last century, as well as the prospects for its continued growth, has singled it out as a viable option for local development, especially in economically poorer countries and regions which are nevertheless rich in their natural and cultural diversity. Based upon an exploratory study of a specific reality, this work aims to collaborate towards a better understanding of the tourism phenomenon and its possible contribution to promoting local development according to the principles of sustainability. Using the case study method, it takes a close look at a particular area, the municipality of Itatiaia in the Brazilian state of Rio de Janeiro, within the Mata Atlántica Biosphere Reserve. The small town of Itatiaia was officially declared a tourist point by the Brazilian government organization EMBRATUR due to its magnificent scenery and to the presence of Brazil s first National Park, which was created in 1937 making the place quite well known nationally and internationally in the tourism context. Other important tourist attractions are found in the town of Penedo which owes its origin to a Finnish settlement, as well as in the rural zones of Maringá and Maromba. This diversified set of nature appealing attractions has transformed the locality into one of the major destinations of ecotourism in recent years in the Southeastern region of Brazil, while the place has also become the focus of various state and federal programs which intend to promote local development through tourism. Tourist activity is at present its main source of employment, being the major economic activity in Maringá, Maromba and Penedo. Such magnitude however does not seem to be recognized by local government authorities, who have not offered the needed support for a sustainable development of tourism in the municipality. Like in other destinations, development of tourism in Itatiaia was not followed by investment in infrastructure, which along with uncontrolled and disorderly urbanization, puts its sustainability currently at risk. The strategic role that tourism plays in the area, and the grave social consequences that may result if it declines, must be absorbed by policy-makers as effective actions are urgent. Solving current problems and reevaluating the course of action certainly require the involvement of all social actors who are interested in a permanent planning process in which priorities must be established and decisions must be made so as to guide the construction of a sustainable future for the locality.